Bifacial Dye Membranes: Ultrathin and Free‐Standing although not Being Covalently Bound. Issue 1 (22nd November 2022) - Hupfer, Maximilian L.; Dellith, Jan; Seyring, Martin; Diegel, Marco; Dellith, Andrea; Ghosh, Soumik; Rettenmayr, Markus; Dietzek‐Ivanšić, Benjamin; Presselt, Martin
Abstract: Layers of aligned dyes are key to photo‐driven charge separation in dye sensitized solar cells, but cannot be exploited as rectifying membranes in photocatalysis to separate half‐cells because they are not sufficiently stable. While impressive work on the fabrication of stable noncovalent membranes has been recently demonstrated, these membranes are inherently suffering from non‐uniform orientation of the constituting dyes. To stabilize layers made from uniformly assembled and aligned dyes, they can be covalently cross‐linked via functional groups or via chromophores at the expense of their optical properties. Here stable membranes from established dyes are reported that do not need to be elaborately functionalized nor do their chromophores need to be destroyed. These membranes are free‐standing, although being only non‐covalently linked. To enable uniform dye‐alignment, Langmuir layers made from linear, water‐insoluble dyes are used. That water‐soluble charge transfer dyes adsorb onto and intercalate into the Langmuir layer from the aqueous subphase, thus yielding free‐standing, molecularly thin membranes are demonstrated. The developed bifacial layers consist almost entirely of π‐conjugated units and thus can conduct charges and can be further engineered for optoelectronic and photocatalytic applications. Abstract : The use of template layers for extension of Langmuir‐Blodgett and related techniques to utilize water‐soluble dyes for the synthesis of quasi‐two‐dimensional molecular layers at the water‐air interface is . Bilayers and intercalated layers stable enough to span 25 µm × 25 µm meshes, although not covalently bonded, are demonstrated. Scalable fabrication of these broadly absorbing pi‐conjugated films is realized via a modified roll‐to‐roll process.